Incorporation of core–shell particles into methacrylate based composites for improvement of the mechanical properties1. Issue 29 (7th August 2015) - Sandmann, Benedict; Happ, Bobby; Perevyazko, Igor; Rudolph, Tobias; Schacher, Felix H.; Hoeppener, Stephanie; Mansfeld, Ulrich; Hager, Martin D.; Fischer, Urs K.; Burtscher, Peter; Moszner, Norbert; Schubert, Ulrich S.
<x xml:space="preserve">Abstract</x> Core–shell particles (soft PBA core and hard PMMA shell) were incorporated into methacrylate based composites. By the incorporation of the polymer lattices the fracture toughness and E-modulus values were improved.